Optical characterization of one dental composite resin using bovine enamel as reinforcing filler - Tribioli, J. T.; Jacomassi, D.; Rastelli, Alessandra Nara de Souza [UNESP]; Pratavieira, S.; Bagnato, V. S.; Kurachi, C. (SPIE, the international society for optics and photonics, 2012)
The use of composite resins for restorative procedure in anterior and posterior cavities is highly common in Dentistry due to its mechanical and aesthetic properties that are compatible with the remaining dental structure. Thus, the aim of this study was to evaluate the optical characterization of one dental composite resin using bovine enamel as reinforcing filler. The same organic matrix of the commercially available resins was used for this experimental resin. The reinforcing filler was obtained after the gridding of bovine enamel fragments and a superficial treatment was performed to allow the adhesion of the filler particles with the organic matrix. Different optical images as fluorescence and reflectance were performed to compare the experimental composite with the human teeth. The present experimental resin shows similar optical properties compared with human teeth. © 2012 SPIE.
Keywords: Composite resin; fluorescence; optical phenomena; Aesthetic property; Bovine enamel; Composite resins; Dental composite resins; Filler particles; Gridding; Human teeths; Optical characterization; Optical image; Optical phenomena; Organic matrix; Reinforcing fillers; Superficial treatments; Adhesion; Dental composites; Dentistry; Enamels; Fluorescence; Geometrical optics; Mammals; Mechanical properties; Optical properties; Resins